Pendidikan Agama Kristen dalam Keluarga di Era Digital Membangun Remaja Bijak Menggunakan Media Sosial - Meilani, Meilani; Fernando, Andreas (Sekolah Tinggi Teologi Kanaan Nusantara, 2022)
The presence of social media as one of the technological advances has changed the way the world communicates and shares information. The development of this technology accelerates and facilitates human access from any part of the world in communicating, but also brings negative impacts and dangers to its users, especially teenagers as the highest users of social media. Teenagers who are unstable individuals, will be very easily affected by the bad influence of the content displayed on social media. The purpose of this writing is to examine the phenomenon that arises in teenagers due to social media, also explaining that the Christian family plays a role to build teenagers to be wise in using social media. Research methods are literature studies with qualitative approaches. The result of this study is that first, parents must be the role models in using the social media so that adolescents see real wise actions in using the internet. Second, directed surveillance of adolescent activities in cyberspace must be carried out by parents to protect and build their level of vigilance when accessing social media. Third, parents are obliged to direct teenagers to become social media as a tool to strengthen their faith in trust and love for God.AbstrakKehadiran media sosial sebagai salah satu kemajuan teknologi telah mengubah cara dunia berkomunikasi dan berbagi informasi. Perkembangan teknologi ini mempercepat dan mempermudah akses manusia dari belahan dunia manapun dalam berkomunikasi, tetapi juga membawa dampak negatif dan bahaya bagi para penggunanya terutama remaja sebagai pengguna tertinggi media sosial. Remaja sebagai pribadi yang masih labil, akan dengan mudah terdampak pengaruh buruk dari konten yang ditampilkan media sosial. Tujuan penulisan ini adalah untuk meneliti fenomena yang timbul pada remaja akibat media sosial, juga menjelaskan peran PAK keluarga dalam membangun remaja menjadi bijak menggunakan media sosial yang ada. Metode penelitian ini adalah melalui studi pustaka dengan pendekatan kualitatif. Hasil dari penelitian ini pertama, orangtua harus menjadi panutan dalam menggunakan media sosial agar remaja melihat tindakan bijak yang nyata dalam menggunakan internet. Kedua, pengawasan terarah terhadap aktivitas remaja di dunia maya harus dilakukan oleh orangtua untuk melindungi mereka dari kejahatan di dunia maya ketika mengakses media sosial. Ketiga, orangtua wajib mengarahkan remaja untuk menggunakan media sosial sebagai alat untuk tujuan membangun kerohanian, memperkuat iman dan kasih mereka kepada Allah.